A Review on Natural Plants for Phytochemical Constituents and Pharmacological Activities - Muni Raja Lakshmi, K; Kiran, M.; Sai Prasanna, K. (Journal of Drug Delivery and Therapeutics, 2021)
The present review aims for the study of phytoconstituents and pharmacological activities of some natural plants. The traditional medicinal plants have been found to acquire therapeutic activities significantly antimicrobial, anti-inflammatory antibacterial, anti-fungal, antioxidant properties etc. The plant-derived constituents are majorly for the aliments of used skin disease diabetes, bronchitis, asthma, arthritis, dry cough, ulcer and fever. The antimicrobial activity of the following plants like Justicia adathoda, Lantana Camara, Acacia leucophloea, Holoptelea integrifolia, Calotropis Procera, chlorophytum tuberosum, Bombax ceiba, Bacopa monnieri, Wedelia trilobata, Jatropha gossypifolia were obtained from the extraction of either  leaves, stem or flowers by using ethanol, methanol, aqueous, petroleum ether, chloroform. The phytochemical constituents of the extract have been shown the presence of alkaloids, glycosides, cardiac glucosides tannins, proteins, carbohydrates, saponin, quinines, triterpenes, steroids, polyphenolic, volatile oil, phenols, starch sugar, amino acid, resin and organic acids. This study evidenced the possible use of the mentioned plants as a source of natural medicines which are used as an antimicrobial, anti-inflammatory, anti-bacterial, anti-fungal, antioxidant agents.Keywords:  Medicinal plants, Antimicrobial, Anti-inflammatory, Antioxidants.